Flavonoids in Ecuadorian Oreocallis grandiflora (Lam.) R. Br.: Perspectives of Use of This Species as a Food Supplement. (11th December 2018) - Vinueza, Diego; Yanza, Karina; Tacchini, Massimo; Grandini, Alessandro; Sacchetti, Gianni; Chiurato, Matteo Andrea; Guerrini, Alessandra
Abstract : Oreocallis grandiflora (Lam.) R. Br. is an Ecuadorian species belonging to the Proteaceae family, commonly known as cucharillo (Loja and Zamora provinces), cucharilla (Sierra region), gañal (Bolívar province), and algil (Chimborazo province). Its leaves and flowers, collected during blooming, are traditionally used for oral administration to treat liver diseases, vaginal bleeding, and ovary/uterus inflammation and as digestive, diuretic, and hypoglycemic remedy. Related literature does not report any scientific evidences regarding the chemical composition of the used parts of this species (leaves and flowers), while few indications are reported about the healthy properties of their preparations. Based on these premises, the present research was performed with the objectives to fill the gaps of the chemical and biological knowledge about this species, enriching the knowledge related to the plant biodiversity of Amazonian Ecuador and to the ethnobotanical tradition of Andean communities. Chemical and biological investigation ( in vitro antioxidant and anti-inflammatory activity) of flower and leaf hydroalcoholic extracts shed a light on the functional metabolites putatively involved in healthy properties of the O. grandiflora traditional preparations. The chemical fingerprinting achieved by HPTLC and 1 HNMR analyses showed the presence of flavonoids, subsequently quantitatively estimated by AlCl3 complexation assay and HPLC-DAD. Silica gel chromatography allowed the isolation of the main compounds of the flower extract: quercetin 3-O- β -glucuronide and myricetin 3-O- β -glucuronide. RP-HPLC-DAD-MS analyses showed the presence of quercetin 3-O-rutinoside and isorhamnetin 3-O-rutinoside, in addition to the above-mentioned molecules, in the leaf extract. Regarding the antioxidant (DPPH test, a radical scavenging assay) and anti-inflammatory (WST-1 assay, an oxidative burst test) activities, leaf extract showed the most promising results when compared to the positive controls. The same extract, however, exhibited a higher cytotoxicity compared to the flower extract, indicating the latter preparation as the most interesting anti-inflammatory crude drug.